Development of the Interactive Whiteboard Acceptance Scale (IWBAS): An Initial Study - Wong, Kung-Teck; Teo, Timothy; Goh, Pauline Swee Choo (Educational Technology ＆ Society, 2014)
The purposes of this study were to develop and to conduct an initial psychometric evaluation of the Interactive Whiteboard Acceptance Scale (IWBAS). The process of item-generation for the IWBAS was carried out through the sequential mixed-method approach. A total of 149 student teachers from a teacher-education institution in Australia participated in the project. The principal component analysis (PCA) yielded a five-factor model comprising 14 items, and its factorial validity was confirmed through the use of confirmatory factor analysis (CFA) using structural equation modelling (SEM). The IWBAS reached the minimum thresholds for an acceptable model fit. In addition to the factorial validities, the convergent validity and discriminant validity of the IWBAS were examined, both showing satisfactory validity and good internal consistency for all five constructs. On this basis, the IWBAS can be considered a valid and reliable instrument designed specifically for assessing IWB acceptance among student teachers.